2011
DOI: 10.1186/1471-2164-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal distribution of RNA expression levels in human skeletal muscle tissue

Abstract: BackgroundMany human diseases and phenotypes are related to RNA expression, levels of which are influenced by a wide spectrum of genetic and exposure-related factors. In a large genome-wide study of muscle tissue expression, we found that some genes exhibited a bimodal distribution of RNA expression, in contrast to what is usually assumed in studies of a single healthy tissue. As bimodality has classically been considered a hallmark of genetic control, we assessed the genome-wide prevalence, cause, and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Thus, future expression studies in the elderly might also help providing new insights into the genetic associations of important disease phenotypes in this population. For instance, the authors of the aforementioned study found that insulin sensitivity was higher in those individuals with the low mode of ACTN3 expression (Mason et al 2011).…”
Section: Research Gaps In the Field And Recommendationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, future expression studies in the elderly might also help providing new insights into the genetic associations of important disease phenotypes in this population. For instance, the authors of the aforementioned study found that insulin sensitivity was higher in those individuals with the low mode of ACTN3 expression (Mason et al 2011).…”
Section: Research Gaps In the Field And Recommendationsmentioning
confidence: 98%
“…Nonetheless, ideally this would require collecting skeletal muscle biopsies, which might not be easily feasible in the elderly. The relevant information that can be obtained with gene expression studies is best exemplified by a recent study on the RNA expression of 17,881 genes at the skeletal muscle level in a cohort of healthy Pima Indians (age range 18-50 years) (Mason et al 2011). Using exon array expression chips, the authors found ACTN3 to be one of the only eight genes that showed bimodal expression.…”
Section: Research Gaps In the Field And Recommendationsmentioning
confidence: 99%
“…This is exemplified by THNSL2 (in the bottom left panel of Figure 4D), whose bimodal expression has been linked to a cis-eQTL in muscle tissue. 25 A c c e p t e d M a n u s c r i p t 10 For more examples, see Table S12.…”
Section: Specific Differential Methylation Correlates With Expressionmentioning
confidence: 99%
“…Gene expression signals were normalised using the robust multichip average method [20] and GC correction. The parameters of the best-fitting bimodal distribution were estimated by maximum likelihood methods after transforming expression data to correct for skewness using the most appropriate Box-Cox parameter, as previously described [10,21]. Individuals were classified into high and low expression categories of HLA-DRB1 based on these parameters [10].…”
Section: Derivation Of Analytical Samples the Analytical Groups Inmentioning
confidence: 99%
“…The expression levels of several skeletal muscle mRNA transcripts in the exon array study had a bimodal frequency distribution, and these transcripts were found to be highly significant expression quantitative trait loci (eQTL), one of which was transcribed from HLA-DRB1 [10]. The aim of the present study was to assess genetic variation at the HLA-DRB1 region and determine its possible role in gene expression and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 96%